Optimal Placement of Distribution Generator by Incorporating Demand Response Strategy for Residential and Industrial User - Shanmugapriya, P.; Kumaran, M.Senthil; Baskaran, J.; Nayanatara, C.; Sharmila, P. (2021 4th International Conference on Computing and Communications Technologies (ICCCT), 2021)
Demand response strategy mainly focuses in reducing the peak demand of the end user by proper scheduling of the appliances which is differentiated as elastic and fixed load by the customer. Demand side management (DSM) lets the customers to minimize the energy consumption and reshapes the load profile. This scheduling is also based on categorizing the devices for whole day in 24 hours duration according to the customer comfort. For execution of the proposed model the entire formulation is conducted by the heuristic approach. Genetic algorithm (GA) is a potent method to get near ideal answer. The impact of the proposed model is studied by simulating on a IEEE - 9 bus distribution system.